2008
DOI: 10.1128/mcb.01607-07
|View full text |Cite
|
Sign up to set email alerts
|

Di- and Tri- but Not Monomethylation on Histone H3 Lysine 36 Marks Active Transcription of Genes Involved in Flowering Time Regulation and Other Processes in Arabidopsis thaliana

Abstract: Histone lysines can be mono-, di-, or trimethylated, providing an ample magnitude of epigenetic information for transcription regulation. In fungi, SET2 is the sole methyltransferase responsible for mono-, di-, and trimethylation of H3K36. Here we show that in Arabidopsis thaliana, the degree of H3K36 methylation is regulated by distinct methyltransferases. The SET2 homologs SDG8 and SDG26 each can methylate oligonucleosomes in vitro, and both proteins are localized in the nucleus. While the previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
318
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(355 citation statements)
references
References 69 publications
31
318
2
4
Order By: Relevance
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 61%
“…The substrate specificities and mutant transcriptional profiles have been previously described for two other Arabidopsis histone methyltransferases: ATX1/SDG27 (H3K4me) and the ASHH2/ SDG8 (H3K36me) (19,27). If SDG2 is functionally similar to ATX1 or ASHH2, one might expect similar transcriptional changes in these mutants.…”
Section: Sdg2 Is Required For the Normal Expression Of A Large Number Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, JMJ706 may play a role in the conversion between H3K36me1 and H3K36me2. It has recently been shown that H3K36me1 has different function than H3K36me2/me3 in transcriptional regulation in plants (28). Although rice JMJ706 is constitutively expressed (Fig.…”
Section: Discussion Specific Features Of Plant Jmjc Domain Protein Gementioning
confidence: 99%
“…H4K16ac is positively correlated with active marks (H3K9ac, H3K18ac, H3K4me2/3 and H3K36me2/3 15,[42][43][44] ) and anti-correlated with repressive modifications (H3K27me1 and H3K9me2 15,45 ) and histone variants H3.1 and H2A.W, which are required for heterochromatin condensation ( Fig. 2A).…”
Section: Combined Enrichment Of H4k16ac and H3k23ac Is Correlated Witmentioning
confidence: 99%